2006
DOI: 10.1001/archopht.124.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Peak Intraocular Pressure During Sleep in Reproduced Diurnal Changes by Posture

Abstract: Objective: To characterize diurnal intraocular pressure (IOP) changes in primary open-angle glaucoma by reproducing IOPs based on patient posture. Methods: In 148 patients with untreated primary openangle glaucoma who had IOPs recorded during clinic hours that were less than 21 mm Hg (average, 14.8±3.2 mm Hg), we measured IOP by noncontact tonometry every 2 hours from 6 AM to midnight and every 3 hours from midnight to 6 AM with patients sitting and supine. The IOP was reproduced by designating the sitting IOP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 19 publications
3
39
0
4
Order By: Relevance
“…The present study showed that the diurnal curve between 8 a.m. and 4 p.m., performed in the supine position, presented higher absolute values for IOP (on average 4 mmHg higher) compared to those in the sitting position (p<0.0001) ( Table 3 and Figure) which corroborated with previous studies (12,24) . After evaluating 198 patients with POAG, Hara et al evaluat observed a difference of 2.9 mmHg between the pressure peaks of the SDTC in the sitting and supine positions (24) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study showed that the diurnal curve between 8 a.m. and 4 p.m., performed in the supine position, presented higher absolute values for IOP (on average 4 mmHg higher) compared to those in the sitting position (p<0.0001) ( Table 3 and Figure) which corroborated with previous studies (12,24) . After evaluating 198 patients with POAG, Hara et al evaluat observed a difference of 2.9 mmHg between the pressure peaks of the SDTC in the sitting and supine positions (24) .…”
Section: Discussionsupporting
confidence: 92%
“…After evaluating 198 patients with POAG, Hara et al evaluat observed a difference of 2.9 mmHg between the pressure peaks of the SDTC in the sitting and supine positions (24) . Liu et al studied 16 youths with healthy eyes and noticed an a verage difference of 4.5 mmHg in the SDTC measurements in both positions.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27] At present there is lack of consensus on the 24-h IOP characteristics of NTG patients. [28][29][30][31][32][33] Some investigators report that peak IOP in NTG occurs at nighttime. 31,33 Others, however, disagree suggesting that most NTG patients exhibit their peak 24-h IOP at daytime.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32][33] Some investigators report that peak IOP in NTG occurs at nighttime. 31,33 Others, however, disagree suggesting that most NTG patients exhibit their peak 24-h IOP at daytime. 30,34 Besides differences in study design and populations, a further reason for such discrepancies in the literature may stem from the fact that systemic medications (prescribed for cardiovascular conditions) can meaningfully influence circadian IOP and OPP rhythm.…”
Section: Introductionmentioning
confidence: 99%
“…(2)(3)(4)(5)(6) Some authors have suggested that nocturnal IOP is higher than in the waking periods.…”
Section: Introductionmentioning
confidence: 99%